Rancang Bangun Sistem IoT Monitoring Pemakaian Daya Listrik dan Air Mesin Cuci Laundry Komersial - Suitbertus Anang Wijayanto; Setiyo Adi Nugroho; Priyadi Priyadi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Monitoring electricity and water consumption of washing machines in laundry businesses poses a distinct challenge for laundry owners. This research aims to develop an IoT-based monitoring system for electrical power and water consumption on washing machines using an ESP32, a PZEM-004T sensor, and a YF-S201 water flow sensor. The data captured by the sensors was stored in a MySQL database server via the MQTT protocol and displayed on a monitoring web page built with CodeIgniter, as well as on a Virtuino IoT Android application. The results showed that the electrical sensor was capable of measuring electrical quantities with a reading error rate of 0.5–1% compared to a digital kWh meter. Similarly, the water flow sensor was able to measure water volume with an error rate of approximately 0.2%. The web-based monitoring dashboard can display data and graphs of electricity and water usage, enabling laundry owners to perform analyses for decision-making in future business development. Sensor data storage from the ESP32 to the MySQL server was successfully executed in real-time with a 1-second time delay. Thus, this IoT implementation successfully provides a real-time and accurate operational monitoring system for washing machines.